2012
DOI: 10.1074/mcp.o112.018366
|View full text |Cite
|
Sign up to set email alerts
|

Global Identification and Characterization of Both O-GlcNAcylation and Phosphorylation at the Murine Synapse

Abstract: O-linked N-acetylglucosamine (O-GlcNAc) is a dynamic, reversible monosaccharide modifier of serine and threonine residues on intracellular protein domains. Crosstalk between O-GlcNAcylation and phosphorylation has been hypothesized. Here, we identified over 1750 and 16,500 sites of O-GlcNAcylation and phosphorylation from murine synaptosomes, respectively. In total, 135 (7%) of all O-GlcNAcylation sites were also found to be sites of phosphorylation. Although many proteins were extensively phosphorylated and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
416
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 375 publications
(460 citation statements)
references
References 65 publications
26
416
4
1
Order By: Relevance
“…We believe that this constitutes the first broad proteomic analysis of O-GlcNAc-modified proteins in primary human T cells. Many of the proteins that we identified appeared in prior proteomics studies (55,(76)(77)(78), supporting the validity of our results. However, we also identified novel O-GlcNAc substrates, including ARNT, HCLS1, ZAP-70, SHIP1, LCK, and PI3K.…”
Section: Discussionsupporting
confidence: 87%
“…We believe that this constitutes the first broad proteomic analysis of O-GlcNAc-modified proteins in primary human T cells. Many of the proteins that we identified appeared in prior proteomics studies (55,(76)(77)(78), supporting the validity of our results. However, we also identified novel O-GlcNAc substrates, including ARNT, HCLS1, ZAP-70, SHIP1, LCK, and PI3K.…”
Section: Discussionsupporting
confidence: 87%
“…S18), or in other words when the residue affected is followed by a Pro. Since in all vertebrates more than 40% of Ser/Thr residues that are phosphorylated are followed by Pro at P+1 (28), reciprocal phosphorylation/O-GlcNAcylation crosstalk, as suggested previously (12), is much more restricted and less frequent than initially proposed.…”
Section: Discussionmentioning
confidence: 79%
“…Thus, doubt still exists as to whether on a specific protein molecule O-GlcNAcylation directly affects phosphorylation or vice versa. Work by Trinidad et al (12) suggested that phosphorylation and O-GlcNAcylation occur randomly with respect to each another and that negative crosstalk is likely not a common phenomenon. From that work it can be hypothesized that phosphorylation/O-GlcNAcylation crosstalk is not really widespread.…”
mentioning
confidence: 99%
“…However, the recent development of lectin weak affinity chromatography (LWAC) and chemical/enzymatic tagging strategies has facilitated enrichment of these modified peptides from complex proteolytic digest mixtures (9,10), and the advent of electron transfer dissociation (ETD) mass spectrometry has facilitated the robust assignment of modification sites (11). These advances have been used effectively for studies in mammalian systems, and over 1,000 O-GlcNAc-modified proteins have been identified (9)(10)(11)(12)(13)(14). However, no similar study has been reported in plants, and thus it's unclear whether O-GlcNAc modification controls similar cellular process in plants and animals.…”
mentioning
confidence: 99%